Hybrid coronary revascularization versus percutaneous coronary intervention: A systematic review and meta-analysis. (December 2021) - Van den Eynde, Jef; Sá, Michel Pompeu; De Groote, Senne; Amabile, Andrea; Sicouri, Serge; Ramlawi, Basel; Torregrossa, Gianluca; Oosterlinck, Wouter
Graphical abstract: Highlights: Hybrid coronary revascularization (HCR) for multivessel disease (MVD) is emerging. This meta-analysis compared HCR to percutaneous coronary intervention (PCI) Both procedures had comparable 30-day outcomes. HCR had less myocardial infarction and target vessel revascularization at follow-up. More randomized controlled trials comparing both approaches are needed. Abstract: Background: Hybrid coronary revascularization (HCR) is an emerging approach for multivessel coronary artery disease (MVD) which combines the excellent long-term outcomes of surgery with the early recovery and reduced short-term complications of percutaneous coronary intervention (PCI). Here, we evaluated the effectiveness of HCR compared to PCI in patients with MVD. Methods: A systematic database search in PubMed/MEDLINE, Embase, Scopus, and CENTRAL/CCTR was conducted by June 2021. Random-effects meta-analysis was performed, comparing major adverse cardiac and cerebrovascular events (MACCE) at 30 days and at latest follow-up between patients undergoing HCR versus PCI. Results: A total of 27, 041 patients (HCR: 939 patients, PCI: 26, 102 patients) were included from seven studies published between 2013 and 2021. At latest follow-up, HCR was associated with lower rates of myocardial infarction (OR 0.40, 95% CI 0.20–0.80, p = 0.010) and target vessel revascularization (OR 0.49, 95% CI 0.37–0.64, p < 0.001), while the difference for MACCE did not reach statistical significance (OR 0.46, 95% CI 0.20–1.05, p = 0.061). No differences were observed in terms of 30-day outcomes, nor rates of mortality or stroke at latest follow-up. Conclusions: HCR might be a valid alternative to multivessel PCI, demonstrating a lower incidence of MI and TVR. Center experience, well-coordinated heart team discussions, and good patient selection likely remain essential to ensure optimal outcomes. Future comparative studies are required to define the optimal target population.